Relação da condição de escore corporal com fatores reprodutivos em vacas sem raça definida do Brejo paraibano - Santos, Jayne Kelly (2021)
The physical condition of the animal has a significant influence on reproductive physiology, so it can be said that nutrition is directly linked to reproduction. One way to assess the physical condition of cattle is through the method of body condition score (ECC). Thus, the objective was to demonstrate the interaction between ECC parameters, oocyte quality, ovarian and follicular diameter, quantity of tertiary follicles and integrity of grade I quality oocyte membrane, in mixed breed cows. Fifty crossbred cows were used, classified according to their ECC (1-5), their respective ovaries were collected, which were analyzed for the number of follicles, and the diameter of the ovarian and follicles. Then, the oocyte was classified according to quality (quantification of cumulus oophorus cells; I-IV) and cell viability (membrane integrity, by propidium iodide). Non-significant results were obtained between body scores in reproductive performance, however, animals with ECC 4 had a greater dominant follicular diameter, and ECC2 obtained a greater amount of oocytes classified as grade IV, considering the need for further studies with animals that present the same age and same estrous phase. When assessing membrane integrity, 58% of oocytes classified as grade I had a membrane lesion, concluding that stereoscopic evaluation alone is not enough to guarantee total viability for the use of reproductive biotechniques.